A pilot study exploring the use of a telephone-assisted planning intervention to promote parental support for physical activity among children and youth with disabilities. (September 2017) - Tanna, Sunita; Arbour-Nicitopoulos, Kelly; Rhodes, Ryan E.; Bassett-Gunter, Rebecca
Abstract: Parent support is an important contributor to physical activity (PA) among children and youth with disabilities (CYD). Although many parents of CYD are motivated to provide parent PA support, CYD remain insufficiently active. The multi-process action control model has been applied to understand parent PA support and highlights behavioral regulation strategies such as action and coping planning as critical for translating intentions into behavior. Parents may struggle to create and carryout planning without support. There is no known research examining telephone support as a tool to promote planning and subsequent parent PA support behavior. Method: Parents (43 mothers and 6 fathers) of CYD (child M age  = 12.53 years ± 5.53; 75% male; 38.6% developmental disability) completed a baseline questionnaire and were subsequently randomized to a telephone-assisted planning experimental group twice over four weeks ( n  = 23) or a control group who had access to planning tools but no telephone assistance ( n  = 26). Results: No significant main or interaction effects emerged for parent PA support behavior. However, a significant time × condition interaction was found for behavioral regulation strategies (i.e., action and coping planning and self-monitoring; F(1, 44) = 5.05, p  = 0.03) indicating a significant increase in the use of behavioral regulation strategies for parent PA support from baseline, for parents assigned to the telephone-assisted intervention. Conclusion: These findings suggest potential for planning support as a tool to enhance behavioral regulation strategies related to parent PA support among parents of CYD. Highlights: Planning for physical activity (PA) support for children with disabilities explored. Telephone support was effective in supporting planning for parent PA support. Planningwas effective for increasing behavioral regulation strategies. Behavioral regulation strategies were correlated with parent PA support behavior. Parent PA support behavior did not change following telephone-assisted planning.